52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0879
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Acoustic Phenomena of Supersonic Jet Impinging on Inclined Flat Plate

Abstract: Acoustic and flow fields of a Mj = 1.8 correctly-expanded jet impinging on a 45 ○ inclined flat plate are investigated experimentally. In the experiments, microphone measurement, Schlieren visualization, and wall static pressure measurement on the inclined plate surface are conducted for different nozzle-plate distances. When the nozzle-plate distance is 5D, two types of acoustic waves, whose characteristics are different in propagation directions, spectra, and source locations, are observed. One propagates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Indeed the jet potential core length of x/D ∼ 10 is well predicted, and the jet is correctly expanded with no intense shock predicted inside the potential core zone (though some shock train is still formed inside the jet) as is well observed in the experimental studies. 39 In comparison with the measured Mach profile, the predicted Mach number falls off more quickly outside of the jet potential core zone with the HRLES simulations doing slightly better than the (steady) RANS simulations. Our preliminary simulations carried out in larger (both axially and radially) domains indicated that the current domain size is adequate.…”
Section: Vb Supersonic Jet Impinging On Inclined Plate Including Inmentioning
confidence: 86%
See 2 more Smart Citations
“…Indeed the jet potential core length of x/D ∼ 10 is well predicted, and the jet is correctly expanded with no intense shock predicted inside the potential core zone (though some shock train is still formed inside the jet) as is well observed in the experimental studies. 39 In comparison with the measured Mach profile, the predicted Mach number falls off more quickly outside of the jet potential core zone with the HRLES simulations doing slightly better than the (steady) RANS simulations. Our preliminary simulations carried out in larger (both axially and radially) domains indicated that the current domain size is adequate.…”
Section: Vb Supersonic Jet Impinging On Inclined Plate Including Inmentioning
confidence: 86%
“…(16). This issue as well as Loci/CHEM validation against the free jet acoustic data available in the literature 39,43 are planned for detailed consideration during next stages of this study.…”
Section: Vb Supersonic Jet Impinging On Inclined Plate Including Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation and verification of the computational code are performed extensively by comparing the measured results of the Me=1.8 perfectly expanded cold impinging jet taken by Nakanishi et al [21,22,40], and measured results taken in the SMAP testing campaign for the free jet, impinging jet on the 45-degree-inclined flat plate, and practical launch pad configurations. In this report, a validation study using the microphone results measured of the practical launch pad configuration shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…14(a), are dominant. [17][18][19][20][21][22] The acoustic wave due to the jet impingement propagates omnidirectionally from the vicinity of the impingement region, and determines the acoustic environment surrounding the vehicle. On the other hand, the Mach wave radiation from the wall jet has a strong directivity at roughly 50 degree from the wall jet axis, so that the effect on the vehicle must be small.…”
Section: Acoustic Design Of Launch Padmentioning
confidence: 99%